Peningkatan Hasil Belajar Peserta Didik pada Pembelajaran Pendidikan Pancasila Menggunakan Metode Card Sort di Kelas V UPT SDN 27 Pasar Kambang Kabupaten Pesisir Selatan - Widari, Rintia Restu; Hamimah, Hamimah; Arwin, Arwin; Zainil, Melva (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to describe the improvement in Pancasila Education learning outcomes through the application of the Card Sort method on fifth-grade students at UPT SDN 27 Pasar Kambang, Pesisir Selatan Regency. The study used a Classroom Action Research (CAR) design with a qualitative and quantitative approach conducted in two cycles. The research subjects included the teacher as the researcher and 22 students consisting of 10 boys and 12 girls. Data were collected through observation of teacher and student activities, attitude assessments, knowledge and skill tests, and learning documentation. Qualitative data analysis was conducted through reduction, presentation, and conclusion drawing, while quantitative data was analysed using percentages and averages to see the improvement in learning outcomes between cycles. The results showed an improvement in the quality of teaching modules, the implementation of learning by teachers and students, learning attitudes, and knowledge and skill outcomes. The average knowledge and skill scores increased from 74.68 in cycle I to 89.22 in cycle II. These findings indicate that the Card Sort method is effective in improving Pancasila Education learning outcomes and encouraging active student involvement in learning.